Surgical Drill Guide for Insertion of an Infra-Acetabular Screw Based on an Anatomically Precontoured Plate System: A Cadaveric Study. (27th July 2021) - Freigang, Viola; Gottsauner, Maximilian; Rupp, Markus; Pfeifer, Christian; Grechenig, Stephan; Kerner, Alexander; Alt, Volker; Baumann, Florian
Abstract : Purpose . Due to the anatomic structure of the pelvis, free-hand placement of screws in the acetabular fracture management can be difficult. Infra-acetabular screw fixation increases acetabular stability by distal fixation of the cup. Aim of this cadaveric study is to investigate if a plate-referenced drill guide can provide save placement of an infra-acetabular screw over a precontoured suprapectineal quadrilateral buttress plate (SQBP). Methods . We constructed a drill guide for an infra-acetabular screw based on the surface of an anatomically precontoured SQBP. A total of 12 adult cadaveric acetabular specimens were used for drill guide-assisted placement of the infra-acetabular screw. The drill guide contains a radiopaque spiral to allow longitudinal fine adjustment of the SQBP along the pelvic brim to assure correct position of the plate-drill-guide construct in relation to the Koehler's teardrop. After screw placement, we conducted a computed tomography (CT) scan of all specimens to assess the actual position of the screw in relation of the infra-acetabular corridor and the acetabular joint surface. Results . The position of the screw was within the infra-acetabular corridor in all cases. We did not see any intra-articular or intrapelvic screw penetration. The mean distance of the centerline of the screw to the medial border of the infra-acetabular corridor was 3.35 mm. The secure distance to the virtual surface of the femoral head to was 7.3 mm. Conclusions . A plate-referenced drill guide can provide safe placement of an infra-acetabular screw for treatment of acetabular fractures. Radiographic fine adjustment is necessary to access the optimal entry point.